Implementasi Hak Waris Perempuan Dalam Masyarakat Adat Patrilineal - Rachelninta, Nathasya Irish; Sulastri, Sulastri (JURNAL USM LAW REVIEW, 2025)
This study aims to analyze the implementation of women's inheritance rights within the patrilineal customary system of Karo ethnic group and the judicial considerations based on the Medan High Court Decision No. 400/Pdt.2023/PT MDN. The urgency of this research lies in harmonizing legal pluralism, particularly the role of judges in inheritance cases and their impact on the development of customary law and gender equality for Karo women and the community. This study employs a normative juridical method to examine the application of customary inheritance law in the distribution of inheritance assets through judicial decisions. The novelty of this research expands on an analysis of the implementation of Karo customary inheritance law in relation to gender equality within civil inheritance law. It refers to the inheritance rights of Karo women in actual cases, distinguishing it from other studies that discuss Karo customary inheritance law or court case resolutions in a purely regulatory manner. The findings reveal that the implementation of Karo women's inheritance rights is reflected in court decisions, where women receive a share, albeit smaller than men, due to differences in rights and obligations. Judges consider customary law as the closest legal framework for the family while also taking gender justice into account by accommodating the inheritance rights of Karo women. The application of Karo customary inheritance law in asset distribution continues to uphold gender fairness for Karo women. This study is expected to contribute both practically and theoretically to the enforcement of a just customary inheritance law. Penelitian ini bertujuan untuk menganalisis implementasi hak waris perempuan dalam masyarakat adat patrilineal, yakni suku Karo, serta pertimbangan Hakim berdasarkan Putusan Pengadilan Tinggi Medan Nomor 400/Pdt.2023/PT MDN. Urgensi penelitian berpusat pada harmonisasi dalam pluralisme hukum, terlebih peran Hakim dalam perkara yang berdampak pada perkembangan hukum adat serta prinsip kesetaraan gender berkeadilan bagi perempuan Karo juga masyarakat. Penelitian ini menggunakan metode yuridis normatif untuk membahas penerapan hukum waris adat dalam pembagian harta waris lewat putusan Hakim. Kebaharuan penelitian memperluas analisis penerapan hukum waris adat Karo dengan kesetaraan gender di dalam hukum waris perdata, mengacu pada hak waris perempuan Karo pada kasus aktual, berbeda dengan penelitian lainnya yang membahas hukum waris adat Karo sebatas regulatif saja. Hasil penelitian menjelaskan implementasi hak waris perempuan Karo tercermin dalam putusan, di mana bagian perempuan lebih sedikit dibanding laki-laki karena perbedaan hak dan kewajiban, serta pertimbangan Hakim merujuk pada pembagian sesuai hukum waris adat sebagai hukum terdekat keluarga, memperhatikan keadilan gender melalui akomodasi akan hak waris perempuan Karo yang diakui. Penelitian ini diharapkan memberikan kontribusi praktis juga teoretis dalam penegakan hukum waris adat yang berkeadilan.